Analysis of the Relationship between Type II Diabetes Mellitus and Parkinson's Disease: A Systematic Review. (23rd November 2019) - Camargo Maluf, Fauze; Feder, David; Alves de Siqueira Carvalho, Alzira
Abstract : In the early sixties, a discussion started regarding the association between Parkinson's disease (PD) and type II diabetes mellitus (T2DM). Today, this potential relationship is still a matter of debate. This review aims to analyze both diseases concerning causal relationships and treatments. A total of 104 articles were found, and studies on animal and "in vitro" models showed that T2DM causes neurological alterations that may be associated with PD, such as deregulation of the dopaminergic system, a decrease in the expression of peroxisome proliferator-activated receptor-gamma coactivator-1 α ( PGC-1α ), an increase in the expression of phosphoprotein enriched in diabetes/phosphoprotein enriched in astrocytes 15 (PED/PEA-15), and neuroinflammation, as well as acceleration of the formation of alpha-synuclein amyloid fibrils. In addition, clinical studies described that Parkinson's symptoms were notably worse after the onset of T2DM, and seven deregulated genes were identified in the DNA of T2DM and PD patients. Regarding treatment, the action of antidiabetic drugs, especially incretin mimetic agents, seems to confer certain degree of neuroprotection to PD patients. In conclusion, the available evidence on the interaction between T2DM and PD justifies more robust clinical trials exploring this interaction especially the clinical management of patients with both conditions.